Communication—CO2 Reduction to Formate: An Electro-Enzymatic Approach Using a Formate Dehydrogenase from Rhodobacter capsulatus. Issue 9 (2nd June 2018) - Choi, Eun-Gyu; Yeon, Young Joo; Min, Kyoungseon; Kim, Yong Hwan
Abstract : CO2 utilization for producing value-added chemicals has recently emerged as a strategy to mitigate atmospheric CO2 levels. Given that (i) certain formate dehydrogenases are capable of interconverting CO2 and formate, and (ii) formate is versatile in various industries, we, herein, aimed to demonstrate FDH-driven formate production from CO2 . Because of its O2 stability, we selected FDH from Rhodobacter capsulatus (RcFDH) and then constructed a mediated electro-enzymatic system. The mediated electro-enzymatic kinetic parameters ( k red and k ox ) were calculated to optimize the reaction conditions favorable for CO2 reduction. Finally, a RcFDH-driven electro-enzymatic system successfully produced 6 mM of formate in 5 hours.